2002
DOI: 10.1093/cercor/12.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit and Saccadic Eye Movement Subregions in Human Frontal Eye Field: A High-resolution fMRI Investigation

Abstract: Recent positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) studies in humans have localized the frontal eye field (FEF) to the precentral sulcus (PCS). In macaque monkeys, low-threshold microstimulation and single unit recording studies have located a saccadic subregion of FEF in a restricted area along the anterior wall of the arcuate sulcus and a pursuit subregion located deeper in the sulcus close to the fundus. The functional organization and anatomical location of these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
96
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 37 publications
12
96
1
1
Order By: Relevance
“…Functional imaging studies of pursuit (e.g. Rosano et al 2002;Petit & Haxby, 1999) and antisaccade performance (e.g. Curtis & D'Esposito, 2003;O'Driscoll et al 1995) in healthy controls do not report significant laterality effects for SEF and FEF oculomotor areas.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Functional imaging studies of pursuit (e.g. Rosano et al 2002;Petit & Haxby, 1999) and antisaccade performance (e.g. Curtis & D'Esposito, 2003;O'Driscoll et al 1995) in healthy controls do not report significant laterality effects for SEF and FEF oculomotor areas.…”
Section: Discussionmentioning
confidence: 84%
“…There was no overlap between this area and that related to antisaccade errors. However, activation studies show that although saccades and smooth pursuit activate the same oculomotor regions, the areas mediating saccades and pursuit are actually distinct and are located in near-by but different areas (Berman et al 1999, Petit andHaxby, 1999;Rosano et al 2002). Berman et al (1999 demonstrated that smooth pursuit and saccades activated the anterior and posterior cingulate cortex with the spatial extent being greater for pursuit in the posterior cingulate, which may have a role in integrating sensory and motor signals, which is especially important for sustained pursuit performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPMC is bounded by FEF (area 8) where the precentral sulcus intersects the superior frontal sulcus and recent work suggests that FEF is contained in the depths of the precentral sulcus (Rosano et al, 2002). On the other hand, two previous reviews of functional imaging data showed that FEF appeared to include the rostral most portion of the precentral gyrus (Paus, 1996;Petit et al, 1999).…”
Section: Rostral Limits Of Lpmcmentioning
confidence: 99%
“…The Frontal Eye Fields (FEF) contain sub-regions for pursuit and saccades (Petit, Clark, Ingeholm, & Haxby, 1997;Petit & Haxby, 1999;Rosano et al, 2002) and previous evidence supports the role of the FEF in memory and more specifically, spatial priming (Offen, Gardner, Schluppeck, & Heeger, O Shea Muggleton Cowey Walsh as neuronal firing often reveals pre-target build-up (Dorris & Munoz, 1998) that is modulated by a previously known target location (Connolly, Goodale, Goltz, & Munoz, 2005). Our MVPA analysis also revealed a significant ability to classify whether the data was from sequence 1 or sequence 4 within this area, indicating that this area is important for the accumulation of information during learning.…”
Section: Multivariate Analysismentioning
confidence: 99%